THE DIFFERENCE LEVEL OF NUTRITIONAL STATUS WITH CLINICAL OUTCOME IN PATIENT WITH ACUTE PHASE ISCHEMIC STROKE - Junaidi, Edwina Narulita Sari Agustin; Winarsih, Sri; Nasution, Tina Handayani (Malang Neurology Journal, 2017)
Background. Nutritional status is predictor that can affects on clinical outcome in patient with acute phase ischemic stroke.Objective. To investigate the difference of nutritional status level with clinical outcome in patient with acute phase ischemic stroke.Methods. Cohort retrospective design used medical record of all registered acute ischemic stroke patient in hospital Dr. Saiful Anwar Malang. 60 sample that inquired inclusion criteria and classified into three groups (the group of patient with acute phase ischemic stroke with normal nutrition status, undernutrition status, and overnutrition status). Nutritional status measured with body mass index parameter and clinical outcome measured with of NIHSS score admission and NIHSS score discharge.Results. There were 60 had good clinical outcome with undernutrition status (n=20) amount 65%, normal nutrition status (n=20) amount 70% and overnutrition status (n=20) amount 60%. The difference of nutritional status level with clininical outcome in patient with acute phase ischemic stroke showed that no significantly difference (chi square, p-value=0,803).Conclusion. There is no difference of nutritional status level with clinical outcome in patient with acute phase ischemic stroke.